2022
DOI: 10.2166/wst.2022.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on fermentative VFAs production from waste sludge stimulated by riboflavin and the shifts of microbial community

Abstract: Fermentative volatile fatty acids (VFAs) production from waste activated sludge (WAS) under moderate temperature is a promising way for resource and energy regeneration in municipal wastewater treatment plants (MWTPs). In this study, the effect of temperature on VFAs production and the associated microbial community from riboflavin-assisted WAS fermentation were investigated. Three fermentative reactors under 25, 35 and 55 °C were operated for 30 days, respectively. The results indicated that riboflavin enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These chemical additives not only stimulated the acidogenic reactions but maximized the key enzymatic activities, reduced lag-phase, and accumulated acidogenic metabolites [59]. Likewise, Liu et al [60] reported that the use of trace metals promoted the abundance of Firmicutes, which play an important role in the acidification process.…”
Section: Biobased Polymersmentioning
confidence: 98%
“…These chemical additives not only stimulated the acidogenic reactions but maximized the key enzymatic activities, reduced lag-phase, and accumulated acidogenic metabolites [59]. Likewise, Liu et al [60] reported that the use of trace metals promoted the abundance of Firmicutes, which play an important role in the acidification process.…”
Section: Biobased Polymersmentioning
confidence: 98%
“…Addition of the redox mediator riboflavin could help synchronize various metabolic processes ( Izadi et al, 2020 ). Previous studies have demonstrated that riboflavin additions to anaerobic cultures can stimulate anaerobic metabolism ( Liu et al, 2022a ), bacterial biofilm formation ( Liang et al, 2021 ), and extracellular electron transfer ( Min et al, 2017 ). Riboflavin also acts as a precursor for flavin mono- and di-nucleotides (FMN and FAD), which serve as coenzymes for proteins involved in fermentation, acetogenesis, and methanogenesis ( Buckel and Thauer, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Residual acidogenic effluents rich in short-chain carboxylic fatty acids/volatile fatty acids (SCCA/VFA) could be effectively treated in various biological/bioelectrochemical processes for the highly valued multiproduct generation, while establishing a carboxylate platform. [10][11][12] Taking advantage of integrating bioprocesses and channelizing them as sequential operational routes considering their individual mechanism/product specificity helps in building a self-regenerative and closed-loop systems. [13,14] Strategical hybridization of bioelectrochemical and conventional fermentation (electrofermentation-EF) due to their synergy could cohesively drive the redox reactions towards targeted product output.…”
Section: Introductionmentioning
confidence: 99%